Contribution of Disaster Response Team in Assisting Natural Disaster Mitigation in Cianjur - Harurikson Lumbantobing; Aryo De Wibowo Sidik; Anggy Pradiftha Junfithrana; Anang Suryana; Handrea Bernando Tambunan; Muchtar Ali Setyo Yudono; Bayu Indrawan; Ilman Himawan Kusumah; Marina Artiyasa; Edwinanto; Yudha Putra; Yufriana Imamulhak (Peneliti Teknologi Teknik Indonesia, 2023)
This article discusses the contribution of the natural disaster response team in assisting with natural disaster mitigation in Cianjur. The disaster response team consists of several experts in the field of electrical engineering, such as electrical technicians, telecommunications specialists, and electronics experts, who are ready to assist in facing natural disasters in the Cianjur region. The article explains the activities carried out by the disaster response team, ranging from pre-disaster preparedness to post-disaster management. Some of the activities performed by the disaster response team include the development and maintenance of electro-technological infrastructure, training and educating the community about natural disaster mitigation, as well as coordination with relevant agencies in disaster management. The results of these activities indicate that the contribution of the natural disaster response team is crucial in assisting with natural disaster mitigation in Cianjur. With the presence of this team, losses can be reduced, and the recovery of the affected areas can be expedited after a disaster. This article can serve as a reference for relevant parties in enhancing preparedness for facing natural disasters in other regions.